A new record of the genus Lissodema Curtis 1833 (Coleoptera: Salpingidae) with description of a new species in Korea. Issue 1 (18th November 2018) - Lee, Seung‐Gyu; Lim, Jongok
Abstract: A genus Lissodema of Salpingidae is first reported from Korea with description of L. dolsandoensis sp. nov. . The new species is compared with related species of the genus. A description, habitus photograph and illustrations of the diagnostic characters are provided.